PERBEDAAN EFEKTIVITAS PERASAN DAN REBUSAN DAUN AGERATUM CONYZOIDES L. TERHADAP PERTUMBUHAN JAMUR TRICHOPHYTON RUBRUM - Moh. Iqbal Firdaus; Siti Roudlotul Hikamah; Diah Sudiarti (Pendidikan Biologi,Universitas Islam Jember, 2017)
This study aims to determine differences in the effectiveness of the juice and decoction of the leaves Ageratum conyzoides L. against Trichophyton rubrum growth. This study is the experimental category. Experiments using completely randomized design (CRD) with three replications and analyzed to determine differences Barriers Minimum Concentration (MIC). The study was conducted in vitro using the method of dilution and methods holes or pitting. Results of the study will be analyzed by ANOVA Test, Duncan and T-Test. Based on the test results of the analysis concludes the difference in effectiveness between the juice and decoction of the leaves Ageratum conyzoides L. Ageratum conyzoides L. leaf Freshly have inhibitory to the growth of the fungus Trichophyton rubrum and (MIC) while the stew is not only on the leaves Freshly Ageratum conyzoides L. Concentration barriers minimum (MIC) Preliminary test (UP) at concentrations of 50% inhibition zone with a diameter of 1.1 cm, while the final test (UA) minimum obstacle concentration (MIC) at a concentration of 40% with a mean diameter of 1.61 cm inhibition zone.Keywords: Ageratum conyzoides L., effectiveness, MIC, Trichophyton rubrum